Penerapan Undang - Undang Darurat Nomor 12 Tahun 1951 Tentang Kepemilikan Senjata Api Secara Ilegal: Putusan Nomor 2157/Pid.Sus / 2017/PN. Mdn - Ridwan Harry Simanungkalit; M. Ridwan Lubis (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Law is defined as a rule or norm that must be followed by humans. To ensure the implementation of law in Indonesia, various legal products are needed, especially laws that regulate community activities. Firearms abbreviated as Senpi are weapons that release one or more projectiles that are propelled at high speed by gas produced by the combustion of a propellant (projectile). The problem of ownership to misuse of firearms is something that is very dangerous and high risk, resulting in fatalities in society, the increasing number of cases in recent years in Indonesia shows the importance of the seriousness of law enforcement in responding to this problem. Misuse of Illegal Firearms Ownership is regulated in Emergency Law Number 12 of 1951 concerning the amendment of the "Ordonnantie Tijdelijke Bijzondere Strafbepalinge" (STBL. 1948 No. 17) and the Former Republic of Indonesia Law Number 8 of 1948 stating that anyone who without the right to enter Indonesia makes, receives, tries to obtain, submits or tries to submit, controls, carries, has a stock of it or has in his possession, stores, transports, hides, uses, or removes from Indonesia a firearm, ammunition or explosive material, is punished with the death penalty or life imprisonment or a temporary prison sentence of up to twenty years. Police Regulation Number 1 of 2022 dated January 28, 2022 concerning licensing, supervision and control of Polri firearms, non-organic TNI-Polri firearms and security equipment classified as firearms, namely non-TNI-Polri firearms with types of non-TNI-Polri firearms including live ammunition firearms, rubber bullets, and gas bullets from the Polri. The process from ordering to handover of goods to the owner, both the legality of documents and physical control (ballistic tests) are under the supervision of the Polri. The circulation of illegal firearms among the Indonesian people requires law enforcement, especially the Police, to be more active and take early prevention measures against those who own, make, and supply illegal firearms that threaten the lives of the community due to the impacts caused by illegal firearm ownership. The case of firearm ownership against the defendant SULIS NURFITO, Ponorogo, 34 years old, Male, Jln. Swadaya Kel. Bukit Batrem District. Dumai Timur Province. Riau, Islam, Construction Workers with Decision NUMBER 2157/Pid.Sus/2017/PN Mdn sentenced to 2 (two) years and 3 (three) months in prison, making the public's perspective on the world of justice in Indonesia far from the public's expectations considering the threat of punishment for the Article applied with the threat of 20 Years in Prison with the verdict given by the judge of 2 (two) years and 3 (three) months shows that law enforcement is far from the public's expectations and does not have a deterrent effect on the defendant and other users of illegal firearms who have not been arrested by the Police.